EFEKTIVITAS PROGRAM PELATIHAN KERJA PADA DINAS PENANAMAN MODAL, PTSP DAN TENAGA KERJA DALAM RANGKA MENURUNKAN TINGKAT PENGANGGURAN DI KABUPATEN BULUKUMBA PROVINSI SULAWESI SELATAN - Udaya Madjid; Andi Ulfiani Umar (Jurnal Academia Praja, 2023)
This study aims to determine how effective the implementation of the Job Training program is in order to reduce the unemployment rate in Bulukumba Regency, supporting and inhibiting factors for program implementation and efforts to overcome these obstacles. The research method used by the author in this study is a qualitative research method with an inductive type of descriptive writing. While the data collection techniques carried out are interviews, observation and documentation. Meanwhile, data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions. The results of this study show that the program to provide training for workers in Bulukumba Regency which has been run since 2016 at the Bulukumba Regency Job Training Center has been carried out well but has not been fully effective.